SUPPORTING REGULATIONS TO IMPLEMENT PERFORMANCE BASED CONTRACT ON ROADS MANAGEMENT - Hendra Hendrawan (Pusbindiklat - LIPI, 2015)
Qualified Road infrastructure is needed to support development acceleration. To improve the quality of road infrastructure reforms needs to be carried out in the field of road management from planning, construction, operation to maintenance. One form of the reform is implementing performance based contract. This paper aims to identify related regulations and criterias those are needed to implement performance based contract optimally. Those regulations were analyzed descriptively and then examined for compliancewiththe performance based contractcriterias. The scope of the regulation are Laws, Goverment Regulation, and Presidential Regulation that related to the implementation of performance based contract. The study showed there has been policy relating to the application of performance based contract. However, these regulations do not meet the criterias necessary for the implementation of performance based contract optimally.